The relation of general socio-emotional processing to parenting specific behavior: a study of mothers with and without posttraumatic stress disorder - Moser, Dominik A.; Aue, Tatjana; Suardi, Francesca; Manini, Aurélia; Sancho Rossignol, Ana; Cordero, Maria I.; Merminod, Gaëlle; Ansermet, François; Rusconi Serpa, Sandra; Favez, Nicolas; Schechter, Daniel S. (Frontiers in Psychology, 2015)
Socio-emotional information processing during everyday human interactions has been assumed to translate to social-emotional information processing when parenting a child. Yet, few studies have examined whether this is indeed the case. This study aimed to improve on this by connecting the functional neuroimaging data when seeing socio-emotional interactions that are not parenting specific to observed maternal sensitivity. The current study considered 45 mothers of small children (12–42 months of age). It included healthy controls (HC) and mothers with interpersonal violence-related posttraumatic stress disorder (IPV-PTSD), as well as mothers without PTSD, both with and without IPV exposure. We found that anterior cingulate cortex (ACC) and ventromedial prefrontal cortex (vmPFC) activity correlated negatively with observed maternal sensitivity when mothers watched videos of menacing vs. prosocial adult male–female interactions. This relationship was independent of whether mothers were HC or had IPV-PTSD. We also found dorsolateral prefrontal cortex (dlPFC) activity to be correlated negatively with maternal sensitivity when mothers watched any kind of arousing adult interactions. With regards to ACC and vmPFC activity, we interpret our results to mean that the ease of general emotional information integration translates to parenting-specific behavior. Our dlPFC activity findings support the idea that the efficiency of top-down control of socio-emotional processing in non-parenting specific contexts may be predictive of parenting behavior.